Professor Sławomir Majewski - Kowalewski, Cezary; Krieg, Thomas; Schwarz, Agatha; Schwarz, Thomas; Orth, Gerard (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Prof. Sławomir Majewski MD, PhD, Head of the Department of Dermatology and Venereology of the Medical University of Warsaw, died on 14 March 2022. He was an outstanding scientist, excellent dermatologist-venereologist, academic teacher, supervisor of many doctoral theses, scientific supervisor and mentor of the specialization of several dermatologists, and author of numerous international publications.